2023
DOI: 10.3389/fimmu.2023.1158105
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants of CTLA4 are associated with clinical outcome of patients with multiple myeloma

Abstract: Immune dysfunction in patients with multiple myeloma (MM) affects both the innate and adaptive immune system. Molecules involved in the immune checkpoint pathways are essential to determine the ability of cancer cells to escape from the immune system surveillance. However, few data are available concerning the role of these molecules in predicting the kinetics of progression of MM. We retrospectively analysed polymorphisms of CTLA4 (rs231775 and rs733618), BTLA (rs9288953), CD28 (rs3116496), PD-1 (rs36084323 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…Interestingly, we did no find differences in cumulative incidence of progression and PFS as it has been previously described for CTLA4 genetic variants ( 25 ). These findings suggest that the studied genotypes of rs1131199 CD200 are not related with the mechanism of escape of cancer cells from immune surveillance control.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Interestingly, we did no find differences in cumulative incidence of progression and PFS as it has been previously described for CTLA4 genetic variants ( 25 ). These findings suggest that the studied genotypes of rs1131199 CD200 are not related with the mechanism of escape of cancer cells from immune surveillance control.…”
Section: Discussionsupporting
confidence: 71%
“…We analyzed the polymorphisms of CTLA4, BTLA, CD28, PD-1 and LAG-3 genes. Our results showed that the CTLA4 genotype identify patients with earlier progression of MM ( 25 ). Based on these interesting findings we decided explored other immune checkpoint molecule as CD200 in the same population.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Gonzalez-Montes et al. identified a CTLA-4 polymorphism (CTLA4 rs231775 AA/AG) that served as an independent predictor of progressive disease ( 66 ). They reported that the AA/AG genotype was associated with median PFS of 32 months vs 96 months for the normal GG genotype while 5-year survival rate was half (25% vs 55%, respectively).…”
Section: Multiple Myelomamentioning
confidence: 99%